Computational topology for approximations of knots - Ji Li; T. J. Peters; K. E. Jordan (Applied General Topology, 2014)
The preservation of ambient isotopic equivalence under piecewise linear (PL) approximation for smooth knots are prominent in molecular modeling and simulation. Sufficient conditions are given regarding: • Hausdorff distance, and • a sum of total curvature and derivative.